2019
DOI: 10.1007/978-3-030-20351-1_42
|View full text |Cite
|
Sign up to set email alerts
|

Riemannian Geometry Learning for Disease Progression Modelling

Abstract: The analysis of longitudinal trajectories is a longstanding problem in medical imaging which is often tackled in the context of Riemannian geometry: the set of observations is assumed to lie on an a priori known Riemannian manifold. When dealing with high-dimensional or complex data, it is in general not possible to design a Riemannian geometry of relevance. In this paper, we perform Riemannian manifold learning in association with the statistical task of longitudinal trajectory analysis. After inference, we o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 14 publications
1
21
0
Order By: Relevance
“…Possible application scenarios include the use of brain MRI to monitor and predict the onset or progression of Alzheimer's disease or other neuro-degenerative disorders to act early and to prevent further progression [22]. Indeed, it has been shown that prediction of the progression in patients with Alzheimer's disease based on variables extracted through deep neural networks might be a promising approach [23][24][25]. Similar needs arise in the progression of patients with liver fibrosis towards liver cirrhosis [26], the progression of osteoporosis [27], the course of cardiovascular diseases [28], or diabetes and its complications [29].…”
Section: Discussionmentioning
confidence: 99%
“…Possible application scenarios include the use of brain MRI to monitor and predict the onset or progression of Alzheimer's disease or other neuro-degenerative disorders to act early and to prevent further progression [22]. Indeed, it has been shown that prediction of the progression in patients with Alzheimer's disease based on variables extracted through deep neural networks might be a promising approach [23][24][25]. Similar needs arise in the progression of patients with liver fibrosis towards liver cirrhosis [26], the progression of osteoporosis [27], the course of cardiovascular diseases [28], or diabetes and its complications [29].…”
Section: Discussionmentioning
confidence: 99%
“…NLMEM include univariate models with time-reparameterizing functions [12]. Multivariate approaches include DIVE [4], a voxel-based model which also clusters disease trajectories, and disease course mapping which combines variations in progression dynamics with phenotypic differences [5,[13][14][15]. In this approach, the observations belong to a Riemannian manifold and each individual trajectory in time is a parallel to a geodesic curve representing the population trajectory.…”
Section: Related Workmentioning
confidence: 99%
“…More recently, deep learning techniques have been proposed for modeling disease progression. Louis et al [207] proposed to use a recurrent neural network to model trajectories of the evolution of cognitive scores and anatomical MRI in patients with AD. Fisher et al [208] used conditional restricted boltzmann machines to generate trajectories of change for different clinical measures in AD.…”
Section: Disease Progression Modelingmentioning
confidence: 99%